Reproductive success of the hybrid tree Dimorphandra wilsonii: implications for conservation - Juliana Ordones Rego; José Neiva Mesquita Neto (Rodriguésia)
Abstract Dimorphandra wilsonii is a rare and endangered tree taxon that was once considered a species, but is now believed to be a hybrid. However, there is no available information on the reproductive status of its remaining populations. Therefore, we aimed to assess the reproductive fitness of D. wilsonii and its implications for the conservation of this endangered tree. We analysed the reproductive system, phenology, seed germination, and seedling development and survival of D. wilsonii, as well as the abundance and behaviour of its floral visitors. Manually self-pollinated and cross-pollinated flowers produced more fruit (0.04% and 0.042%, respectively) than spontaneously self-pollinated flowers (0.01%). Seed germination rates were highest for those pollinated naturally (53.3%) and through cross-pollination (44.2%). However, seedlings resulting from manual self-pollination had the lowest survival rate among treatments (only 5% survived after 180 days). Stingless bees, which generally facilitate self-pollination, were the most likely biotic pollinators. Recent evidence suggests that individuals of D. wilsonii are hybrids resulting from the crossing of two other Dimorphandra species. Our results indicate that existing populations can successfully interbreed and produce offspring. These findings provide insight into the taxonomic and conservation status of D. wilsonii and its parental species.